Transversal magneto-resistance in epitaxial Fe 3O 4 and Fe 3O 4/NiO exchange biased system - SHVETS, IGOR (My University, 2012)
We have investigated transversal magneto-resistance (MR) in epitaxial Fe 3O 4 and Fe 3O 4/NiO exchange biased systems. It was found that the magnetic field dependence and the magnitude of the transversal MR in both systems strongly depend on the bias current density which suggests that the transversal MR in metal oxide with anti-phase boundaries (APBs) cannot be described by the conventional transversal MR for a single magnetic domain. The effect of electron scattering at the APBs may have to be considered. Angular dependence of the transversal MR at low temperature further indicates that the current explanation of the origin of transversal MR on the basis of anisotropic MR alone may not be sufficient for a system experiencing charge ordering.
PUBLISHED
Keywords: transversal magneto-resistance (MR); transversal magneto-resistance (MR)